PEDAGOGICAL PRINCIPLES OF MODELING INTEGRATIVE LESSONS IN FUTURE TEACHERS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article analyzes the pedagogical principles of modeling integrative lessons for future teachers. Integrative education aims to expand the general outlook of students by combining different subjects and fields of knowledge in the educational process. The article discusses the main principles of integrative lessons - interactivity, cooperation, ensuring active participation of students and problem-based approach. Also, the role of teachers in the process of lesson modeling and pedagogical strategies are discussed.